2014
DOI: 10.1071/he14004
|View full text |Cite
|
Sign up to set email alerts
|

Active travel to work in NSW: trends over time and the effect of social advantage

Abstract: Issues addressed: Active travel can increase population levels of physical activity, but should be promoted equitably. Socioeconomic advantage, housing location and/or car ownership influence walking and cycling (active travel) for transport. We examined active commuting over time in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…This finding supports those from Sydney that show slightly higher cycling rates in inner Sydney (within 10 km of the CBD) than in surrounding areas (Zander et al, 2014). These findings may indicate that government investment in bicycle infrastructure within the inner areas of Brisbane has resulted in more transport cycling, and that cycling in outer suburban areas could be potentially increased with such investment.…”
Section: Cycling For Transportsupporting
confidence: 84%
See 3 more Smart Citations
“…This finding supports those from Sydney that show slightly higher cycling rates in inner Sydney (within 10 km of the CBD) than in surrounding areas (Zander et al, 2014). These findings may indicate that government investment in bicycle infrastructure within the inner areas of Brisbane has resulted in more transport cycling, and that cycling in outer suburban areas could be potentially increased with such investment.…”
Section: Cycling For Transportsupporting
confidence: 84%
“…In contrast, in studies from the US (Cervero and Duncan, 2003) and UK (Panter et al, 2013a;Panter et al, 2013b) there was no association found between level of disadvantage and transport cycling. In a recent study from Sydney (Zander et al, 2014); however, there was a dose-response relationship between level of disadvantage and cycling to work, with residents in the most disadvantaged areas being the least likely to cycle to work.…”
Section: Cycling For Transportmentioning
confidence: 91%
See 2 more Smart Citations
“…The design of aesthetically pleasing and practical pedestrian and cycling paths has been clearly shown to increase both physical activity and active travel, yet proximity to destinations remains an important influence on active travel (see Zander et al). 11 Distance from the city centre is adversely associated with adequate physical activity, yet if active travel patterns were to improve, there would be considerable health benefits (see Beavis et al). 12 New research is now extending the traditional health benefits of cycling to links with quality of life measures (Crane et al).…”
mentioning
confidence: 99%